The Effect of Iodium 30c on Experimental Visceral Leishmaniasis - Joshi, Jyoti; Bandral, Chetna; Manchanda, Raj Kumar; Khurana, Anil; Nayak, Debadatta; Kaur, Sukhbir (Homeopathy, 2020)
Background Leishmaniasis is one of several neglected tropical diseases that warrant serious attention. A disease of socio-economically poor people, it demands safer and cheaper drugs that help to overcome the limitations faced by the existing anti-leishmanials. Complementary or traditional medicines might be a good option, with an added advantage that resistance may not develop against these drugs. Thus, the present investigation was performed to evaluate the anti-leishmanial efficacy of an ultra-diluted homeopathic medicine (Iodium 30c) in experimental visceral leishmaniasis (VL).Methods Compliant with strict ethical standards in animal experimentation, the study was performed in-vivo in inbred BALB/c mice which were injected intravenously with 1 × 107 promastigotes of Leishmania donovani before (therapeutic) or after (prophylactic) treatment with Iodium 30c for 30 days. In other groups of mice (n = 6 per group), amphotericin B served as positive control, infected animals as the disease control, while the naïve controls included normal animals; animals receiving only Iodium 30c or Alcohol 30c served as sham controls. The anti-leishmanial efficacy was assessed by determining the hepatic parasite load and analysing percentages of CD4+ and CD8+ T cells. Biochemical analysis and histological studies were performed to check any toxicities.Results Iodium-treated animals showed a significantly reduced parasite load (to 1503 ± 39 Leishman Donovan Units, LDU) as compared with the infected controls (4489 ± 256 LDU) (p < 0.05): thus, the mean therapeutic efficacy of Iodium 30c was 66.5%. In addition, the population of CD4+ and CD8+ T cells was significantly increased (p < 0.05) after treatment. No toxicity was observed, as evidenced from biochemical and histopathological studies of the liver and kidneys. Efficacy of Iodium 30c prophylaxis was 58.3%, while the therapeutic efficacy of amphotericin B was 85.9%.Conclusion This original study has shown that Iodium 30c had significant impact in controlling parasite replication in experimental VL, though the effect was less than that using standard pharmaceutical treatment.
Keywords: Leishmania spp.; visceral leishmaniasis; Iodium 30c; homeopathy; amphotericin B